2021
DOI: 10.31234/osf.io/sfp4x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constructing a graphical model of the relationship between physical activity and cognitive function based on a systematic review of prospective evidence

Abstract: Elucidating the factors that contribute to healthy ageing is an important research goal. Physical activity (PA) has been associated with benefits for cognitive function (CF). However, most of this evidence comes from longitudinal cohort studies which, in the absence of experimental design, have limited scope to make causal inferences regarding observed relationships. This review aimed to utilise recent methodological developments allowing researchers to formulate and answer stronger causal questions using obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This pattern of results was unexpected as it does not align with most of the recent literature that was synthesized and reviewed to construct the conceptual model informing this analysis. 11 However, a minority of the synthesized studies also reported no association between PA and CF 25–28 and, in common with two of these studies, the UK Biobank sample was younger at baseline than most of the other cohorts in which protective effects have been found. Taken together, our findings may suggest that observed associations in older baseline samples reflect reverse causation, whereby some participants had preclinical cognitive decline at baseline.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This pattern of results was unexpected as it does not align with most of the recent literature that was synthesized and reviewed to construct the conceptual model informing this analysis. 11 However, a minority of the synthesized studies also reported no association between PA and CF 25–28 and, in common with two of these studies, the UK Biobank sample was younger at baseline than most of the other cohorts in which protective effects have been found. Taken together, our findings may suggest that observed associations in older baseline samples reflect reverse causation, whereby some participants had preclinical cognitive decline at baseline.…”
Section: Discussionmentioning
confidence: 88%
“…The variables within the conceptual DAG model 11 were matched to the data available within UK Biobank (see Supplementary Methods , available as Supplementary data at IJE online for detail).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations